Strategi Pengelolaan Zakat Berbasis Al-Qur’an: Formulasi Baru untuk Pengentasan Kemiskinan - Siregar, Umar Mukhtar (Al-Kauniyah, 2025)
This study aims to obtain a comprehensive understanding of zakat management by integrating library research with field findings. Data were collected through literature review, observation, and in-depth interviews at the Regional Amil Zakat Agency (BAZDA) of Binjai City, North Sumatra Province, which served as the primary research site and respondent. Using a case study approach, the analysis was conducted in two stages: exploring, which involves breaking down complex phenomena into detailed components, and describing, which reconstructs these components in accordance with scientific analytical standards. All data were analyzed qualitatively and descriptively, referring to relevant theories and positive legal provisions related to zakat. The results show that zakat management at BAZDA Binjai City has been implemented in accordance with Islamic principles and national regulations, particularly Law Number 38 of 1999 on Zakat Management. The management of ZIS is carried out through three main stages: collection, distribution, and utilization of funds. BAZDA Binjai City provides various mechanisms for zakat payment, including direct submission, bank transfers, and collaboration with Zakat Collection Units (UPZ) across multiple institutions. These findings confirm that zakat management by BAZDA Binjai City meets the standards of accountability, legal compliance, and effectiveness in community empowerment.